ANALISIS FAKTOR – FAKTOR YANG BERPENGARUH TERHADAP PROFITABILITAS PERBANKAN YANG GO PUBLIC DI BURSA EFEK INDONESIA PADA TAHUN 2012 - 2016 - Astohar Astohar (Jurnal Dinamika Ekonomi & Bisnis, 2018)
Banking plays a role in economic development, namely in spurring economic growth. The main function of the bank is as a financial intermediary from parties who have excess funds with those who lack funds. The existence of the banking sector has an important role, which in the life of the community mostly involves services from the banking sector. Banking profitability is a ratio to determine the financial performance of banks. Research from Ali and Laksono (2017) is still interesting to develop both the variables and the object of research. In this study, the variable capital adequacy ratio (CAR) added with consideration that there were still differences between researchers.This study took the object of banks going public on the Indonesia Stock Exchange. Banks that went public in 2016 were 43 banks. After checking as many as 26 banks that can be taken as samples through purposive random sampling technique. 17 banks that cannot be used as samples include going public in the year after 2012 and the absence of complete data. The analytical tool used is multiple regression equation test with the requirement to meet normal criteria and no classical assumption deviations occur.The results showed that the capital adequacy ratio (CAR), loan to deposit ratio (LDR), operational costs and operating income (BOPO) proved to have a negative and significant influence on banking profitability. Net interest margin (NIM) is proven to have a positive and significant influence on banking profitability. Non-performing loans (NPLs) are proven to have a negative and insignificant effect on banking profitability. Large variations in capital structure variables in banks that go public in Indonesia can be explained by variations in the variables of capital adequacy ratio (CAR), non-performing loans (NPL), loan to deposit ratio (LDR), operational costs and operating income (BOPO), net interest margin (NIM) is 92.3%.